Implementation of Time Management in the Framework of Optimizing Work - Family Balance in State Wealth Service Office Employees and Denpasar Auction - Ni Luh Ketut Dewi Aryasari (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
This study aims to determine the application of time management in optimizing Work-Family Balance at the Office of State Assets Services and Auctions. This research is motivated by problems that occur at the Denpasar State Property and Auction Services Office, namely problems in the workforce and starting to take time as a serious thing. Employees of the Denpasar State Assets and Auction Services Office find it difficult to manage time between work and family matters. One of the strategies that can be used at the State Property and Auction Services Office is to implement effective time management. This study uses qualitative research methods. Researchers try to describe the application of time management in order to optimize work-family balance based on existing theories in reality in the field. The data source used in this study is using primary sources. Primary sources come from data in the form of opinions and experiences from people who are research subjects. This research data collection technique is through interviews, observation, and documentation. This research is expected to provide value (benefits) and contribution related to the problems that exist in the field. Researchers want to provide benefits both theoretically and practically. Theoretically, this research is expected to be able to provide information and knowledge related to the application of time management in optimizing work-family balance. Practically it can be used as material for consideration or information for companies in dealing with phenomena that occur regarding the application of time management in optimizing work-family balance.